2007
DOI: 10.1074/jbc.m703211200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Basis for (S)-Allantoin Formation in the Ureide Pathway

Abstract: The ureide pathway, which mediates the oxidative degradation of uric acid to (S)-allantoin, represents the late stage of purine catabolism in most organisms. The details of uric acid metabolism remained elusive until the complete pathway involving three enzymes was recently identified and characterized. However, the molecular details of the exclusive production of one enantiomer of allantoin in this pathway are still undefined. Here we report the crystal structure of 2-oxo-4-hydroxy-4-carboxy-5-ureidoimidazoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 31 publications
4
42
0
1
Order By: Relevance
“…On the other hand, the TTL protein contains a sequence resembling a peroxisome targeting signal (Hennebry et al, 2006), and it has been found as a component of Arabidopsis leaf peroxisomes (Reumann et al, 2007). Moreover, structural studies have shown that the Urad domain of TTL binds S-allantoin and has structural similarity to vertebrate OHCU decarboxylase (Kim et al, 2007). Altogether, these observations suggest that the Arabidopsis TTL protein plays a dual role in plant growth, both in modulating brassinosteroid hormone responses and ureide synthesis.…”
Section: Introductionmentioning
confidence: 90%
“…On the other hand, the TTL protein contains a sequence resembling a peroxisome targeting signal (Hennebry et al, 2006), and it has been found as a component of Arabidopsis leaf peroxisomes (Reumann et al, 2007). Moreover, structural studies have shown that the Urad domain of TTL binds S-allantoin and has structural similarity to vertebrate OHCU decarboxylase (Kim et al, 2007). Altogether, these observations suggest that the Arabidopsis TTL protein plays a dual role in plant growth, both in modulating brassinosteroid hormone responses and ureide synthesis.…”
Section: Introductionmentioning
confidence: 90%
“…The modifications were performed using the QuikChange method (Agilent) to introduce a silent mutation at the sequences for NdeI and XhoI sites residing in the internal region of the AtUGlyAH gene. The N-terminal truncated variants of AtUGlyAH, from which the signal peptide (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and an additional N-terminal region had been removed, were amplified using a pair of sequence-specific primers (supplemental Table S1). The resulting PCR products were introduced into the NdeI and XhoI sites of a modified pET-28a vector (Merck) containing a tobacco etch virus protease cleavage site at the junction between a His 5 tag and a multiple cloning site.…”
Section: Methodsmentioning
confidence: 99%
“…During the decarboxylative cleavage of the C1-C2 bond, a negative charge ultimately develops in the form of a C2 carbanion. Many decarboxlases employ cofactors to stabilize carbanion formation (Begley and Ealick, 2004), although cofactorindependent decarboxylases have been recently discovered (Appleby et al, 2000;Harris et al, 2000;Miller et al, 2000;Wu et al, 2000;Cendron et al, 2007;Kim et al, 2007;Chan et al, 2009). 3-Keto acids carry an inherent electron sink in the 3-carbonyl group, a property underlying their implied instability (Jencks, 1969).…”
Section: Online)mentioning
confidence: 99%